2006
DOI: 10.1111/j.1440-1630.2006.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with Parkinson's disease: Elderly patients’ and relatives’ perspective on daily living

Abstract: Background/aim: Parkinson's disease is a progressive neurodegenerative disorder resulting in significant disability. We examined how Parkinson's disease affects daily living from the perspective of both patients and relatives. Methods: Qualitative interviews were performed with seven patients with Parkinson's disease and nine relatives from families other than those of the interviewed patients. Patients and relatives were recruited from an outpatient geriatric unit at a university hospital in Sweden. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 33 publications
5
68
0
7
Order By: Relevance
“…5,8,9 The profile of caregivers in this study is consistent with the research literature 4 with many of them elderly and ill, providing care over an extended period of time. Caregivers experienced an array of emotions such as feelings of helplessness, guilt and feeling emotionally and mentally drained, as illustrated in other research.…”
Section: Discussionsupporting
confidence: 87%
“…5,8,9 The profile of caregivers in this study is consistent with the research literature 4 with many of them elderly and ill, providing care over an extended period of time. Caregivers experienced an array of emotions such as feelings of helplessness, guilt and feeling emotionally and mentally drained, as illustrated in other research.…”
Section: Discussionsupporting
confidence: 87%
“…For example, in some studies, participants described choosing to spend time with people who were in a similar position to them rather than people without PD or impairment (e.g., [88]). Other people lacking understanding or being uncomfortable with PD have been cited as a contributory factor to altered social contacts [89]. Indeed, people with PD have reported benefits from spending time with other people with PD in nonstigmatising contexts such as self-help and therapeutic groups (e.g., [90, 91]).…”
Section: The Psychoemotional Impact Of Stigma Surrounding Pdmentioning
confidence: 99%
“…Indeed, people with PD have reported benefits from spending time with other people with PD in nonstigmatising contexts such as self-help and therapeutic groups (e.g., [90, 91]). Moreover, studies have found that people with PD and their families often avoid social situations due to fear of negative judgement by others [61, 81, 89, 92]. As such, negative and stigmatising public attitudes or action by others are considered to limit social opportunities for people with PD.…”
Section: The Psychoemotional Impact Of Stigma Surrounding Pdmentioning
confidence: 99%
“…First, it focused on the transition related to the moderate stage of the disease among elderly couples. The intervention was developed around this transition, which is a pivotal stage where couples wish to be supported and to learn how to ask for, receive and deliver care, to negotiate jointly several demands and needs at times in conflict with one another, to come to terms with family, friends and healthcare professionals, and to plan their future together (Wressle, Engstrand, & Granérus, 2007). Transitions theory is congruent with the notions of the trajectory of degenerative diseases that affect elderly couples and the timing of the intervention.…”
Section: Accepted Manuscriptmentioning
confidence: 99%